The chromosomal DNA damage in buccal mucosa cells among schools children in the vicinity of mobile base stations in Selangor - Chokeli, Raihanah; Baharuddin, Nur Azira; How, Vivien; Yuswir, Nurul Syazani; Mohd Noor, Shariza Afini; Ho, Yu Bin; Lim, Poh Ying; Jalaludin, Juliana; Hashim, Zailina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The increased use of mobile phones has increased the mobile base stations (MBS) deployment. While understanding of radiation protection is growing among the public, questions regarding early-life exposure to radiofrequency radiation (RFR) from MBS in children are of importance as to whether it will raise the chances of developing chronic diseases during adulthood. Taking into account the sitting location of MBS, the purpose of this study is to evaluate the chromosomal DNA damage in buccal mucosal cells between school children exposed to RFR emitted from base station antennas. Method: This is a comparative cross-sectional study in which two group of school children were sampled i.e. exposed groups are children whose school located near MBS (≤200 meters); unexposed groups are children whose school located distant far from the MBS (>200 meters). Digital RF Analyzer was used to measure RFR at the school surrounding. Buccal mucosa cells from the oral cavity were sampled to examine the level of micronuclei (MN) frequencies. Results: This study found that the densities of the RFR energy differed in range. Although all measurements showed the RFR reading below the acceptable exposure level, there were still significant variations at each location assessed. Statistically, the MN frequency is significantly different when compared to the exposed and non-exposed group. Conclusion: To understand the mechanism of health effects from exposure to low-level RFR emited from MBS, further study should consider environmental factors influencing MBS sitting on RFR emission, as well as examining the health effects into molecular levels.